Pengaruh Endorser pada Media Iklan Televisi terhadap Citra Produk Studi Kasus pada PT. Produk Tolak Angin Sido Muncul - Supariyani, Emmy; Purba, Jan Horas Veriyadi; Rangga, Muhammad (Sekolah Tinggi Ilmu Ekonomi Kesatuan, 2006)
The purpose of research is to comprehend the influence of endorserâs in television advertisement toward product image of Jamu Tolak Angin Sido Muncul. The result of research showed that endorser has a positive influence towards product image, significant with level of confidence 95%. The coefficient correlation is 0.638, means positive and strong correlation. The average of eight items of questionnaires for endorserâs performance is 4.49 in five Linkerâs scale. That means the performance of endorser is categorized as âvery goodâ Keywords: Endorser; Marketing Strategy